A comparative study on the feasibility of introducing a law to regulate retail tenancies in peninsular Malaysia - Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah; Amin, Naemah; Kassim, Salina (UTM Press, 2015)
Malaysia has no special law to regulate retail tenancies unlike the position in Australia and the United Kingdom. Such a situation leaves the landlord-tenant relationship for retail tenancies to be regulated wholly by market forces which may not be able to address power imbalances that may adversely affect the relationship. This article discusses the present tenancy law in Malaysia, identifies gaps, looks at the position in Australia and highlights defining features of the law regulating retail tenancies there. Employing both,quantitative and qualitative research methods, a survey was carried out on landlords and tenants of retail premises in the Klang Valley. The findings reveal that there are various issues and problems arising out of the relationship of landlord and tenant of retail premises in the Klang Valley and that both generally favour proposals to improve this relationship. A majority of respondents are agreeable to a special mediation body for settling retail tenancy disputes so as to avoid court action. Further, a large proportion of respondents are also supportive of a specific law to regulate retail tenancies. The article concludes with recommendations on the defining features of a proposed law to regulate retail tenancies in Peninsular Malaysia.